Tactile Stimulation Evokes Long-Lasting Potentiation of Purkinje Cell Discharge In Vivo - Ramakrishnan, K. B.; Voges, Kai; De Propris, Licia; De Zeeuw, Chris I.; D’Angelo, Egidio (Frontiers in Cellular Neuroscience, 2016)
In the cerebellar network, a precise relationship between plasticity and neuronal discharge has been predicted. However, the potential generation of persistent changes in PC spike discharge as a consequence of plasticity following natural stimulation patterns has not been clearly determined. Here we show that facial tactile stimuli organized in theta-patterns can induce stereotyped NMDA and GABA-A receptor-dependent changes in Purkinje cell (PCs) and molecular layer interneuron (MLIs) firing: invariably, all PCs showed a long-lasting increase (spike-related potentiation or SR-P) and MLIs a long-lasting decrease (spike-related suppression or SR-S) in baseline activity and spike response probability. These observations suggests that natural sensory stimulation engages multiple long-term plastic changes that are distributed along the mossy fiber – parallel fiber pathway and operate synergistically to potentiate spike generation in PCs. In contrast, theta-pattern electrical stimulation of PFs indistinctly induced SR-P and SR-S both in PCs and MLIs, suggesting that natural sensory stimulation preordinates plasticity upstream of the PF-PC synapse. All these effects occurred in the absence of complex spike changes, supporting the theoretical prediction that Purkinje cell activity is potentiated when the mossy fiber - parallel fiber system is activated in the absence of conjunctive climbing fiber activity.